(untitled) (Research, Society and Development, 2020)
In the pharmacological treatment of cancer, drugs with advanced therapeutic performance based on nanotechnologies have shown better performance compared to traditional drugs and among these, liposomal nanocarriers are more effective in directing these therapies to cancer cells, as they are able to make drugs available directly on the affected organs, tissues and cells, providing selectivity and less toxicity. The aim of this study was to evaluate the advantages of using liposomal nanocarriers in drugs used for antineoplastic therapy. This is a review of the literature, carried out by searching for scientific articles in the electronic databases Pubmed, Scielo and Google Scholar, using the terms "liposomes", "nanocarreaes" and "antineoplastic therapy" as descriptors, with a time frame of 2015 to 2020. The results suggest that the use of liposomal nanocarriers applied to drugs for antineoplastic therapy has shown to be a promising technology for its selectivity, non-toxicity, biocompatibility, in addition to being blood-stable, non-immunogenic and biodegradable. However, it is necessary to seek advances in the optimization of its use and its standardization, aiming at greater safety in its use in an attempt to align the innovations in this area with clinical practice.